The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s11064-016-1971-4
|View full text |Cite
|
Sign up to set email alerts
|

Endothelins Inhibit Osmotic Swelling of Rat Retinal Glial and Bipolar Cells by Activation of Growth Factor Signaling

Abstract: Water accumulation in retinal glial (Müller) and neuronal cells resulting in cellular swelling contributes to the development of retinal edema and neurodegeneration. Here, we show that endothelin-1 (ET-1) dose-dependently inhibits the hypoosmotic swelling of Müller cells in freshly isolated retinal slices of control and diabetic rats, with a maximal inhibition at 100 nM. Osmotic Müller cell swelling was also inhibited by ET-2. The effect of ET-1 was mediated by activation of ET and ET receptors resulting in tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
(87 reference statements)
1
1
0
Order By: Relevance
“…Visual system. Similar findings were reported in the visual system, where Vogler et al (35) found that ET-1 inhibits osmotic swelling of rat retinal glial and bipolar cells by activation of growth factors and that this effect was associated with release of ATP and activation of P2Y 1 receptor. Collectively, these findings suggest a potential cooperative interaction between P2 and ET-1 signaling in different physiological functions.…”
Section: Extrarenal Purinergic and Endothelin System Interactionssupporting
confidence: 83%
“…Visual system. Similar findings were reported in the visual system, where Vogler et al (35) found that ET-1 inhibits osmotic swelling of rat retinal glial and bipolar cells by activation of growth factors and that this effect was associated with release of ATP and activation of P2Y 1 receptor. Collectively, these findings suggest a potential cooperative interaction between P2 and ET-1 signaling in different physiological functions.…”
Section: Extrarenal Purinergic and Endothelin System Interactionssupporting
confidence: 83%
“…These cells were collected from transgenic rats carrying a temperature-sensitive SV40 large T-antigen gene [21,22]. The TR-MUL5 cells were cultured in Dulbecco's Modified Eagle's Medium (DMEM) supplemented with 10% fetal bovine serum (FBS) at 33°C in a humidified atmosphere of 5% CO 2 /air.…”
Section: Cell Culturesmentioning
confidence: 99%